TINJAUAN KELENGKAPAN PERSYARATAN KLAIM COVID-19 RAWAT INAP GUNA MENUNJANG MUTU PENGKLAIMAN DI RUMAH SAKIT - Haula Febriani (Jurnal Infokes, 2022)
The purpose of this study is to get an overview of the completeness of the claims file using the 5M element. The research was carried out using descriptive quantitative methods. By describing the results of interviews and observations that have been made. The sample in this study was taken from the claims of inpatient Covid-19 patients at the Hazardngkara TK.II Sartika Asih Hospital in Bandung. From research conducted at Bhayangkara Sartika Asih Hospital, Bandung, there are still problems found, namely: (1) Filling out an incomplete resume, (2) There is a written diagnosis filled in by the DPJP that is not clear and unreadable and medical support that does not include lab and radiology results, (3) Lack of discipline and health personnel to fill out complete medical records in accordance with hospital standard operating procedures (SOP), (4) hardware and software that often experience interference. The suggestions given are: (1) conducting socialization and evaluation of filling out resumes, (2) other medical and health record officers must continue to remind each other in filling out the completeness of medical records and other medical supporting results, (3) Giving warnings and sanctions if mistakes are made. repeated, (4) perform maintenance on hardware and software. Keywords: Completeness of Files, Claim Requirements, Covid-19